IMPROVING THE AERODYNAMIC PERFORMANCE OF THE BLADE OF 3D WIND TURBINE BY DESIGNING THE BLADE GEOMETRY - Alireza SHirzadegan , Reza Aghaei togh, Fereidoon Sabetghadam (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of the study was to present new geometries of wind turbine blades based on natural patterns (like birds) so that the aerodynamic efficiency (ratio of lift to drag coefficient) and optimal pressure coefficient can be obtained. In the next step, the new blades introduced in the present study called swallow geometry blades and seagull geometry blades were modeled and their performance was evaluated and compared with the base blade. This was done numerically in CFX software in two Reynolds numbers 60,000 and 80,000 and at angles of attack from 0 to 20 degrees. According to the studies conducted and the results obtained from the graphs about the condition of the lift, drag and pressure ratios, one can state that the blade with swallow geometry and the blade with seagull geometry can be a good alternative to the blade with NACA 23012 geometry. As a result, it can be said that by replacing these two blades in the construction of 3-blade horizontal axis wind turbines, with small and medium size, a much higher power factor and efficiency can be achieved which can be a big change in the construction of horizontal axis wind turbines with small and medium size.